南极半岛屈韦维尔岛白垩纪中期火山岩浆作用及其构造指示:锆石U-Pb年代学和Hf同位素制约 - 郑光高; 刘晓春; 赵越; 王伟; 陈龙耀 (岩石学报, 2017)
南极半岛长期以来位于冈瓦纳古陆的西缘,是冈瓦纳古陆最后裂解的发生地。南极半岛内出露有大量的中新生代火成岩,关于其成岩期次、源区性质以及产出的动力学背景等尚存争议,从而影响到对南极半岛构造演化的认识。本文报道了南极半岛中部构造域屈韦维尔岛地区出露的安山质火山岩、闪长玢岩脉及其中闪长岩捕掳体的LA-MC-ICP-MS锆石UPb年代学和Hf同位素分析数据。其中含角砾安山质熔岩、安山质火山角砾岩、中粒闪长岩捕虏体和闪长玢岩脉4件样品的锆石U-Pb测年结果分别为103.3±1.7Ma、101.9±1.8Ma、92.0±1.2Ma和85.7±07Ma,表明该岛在白垩纪中期存在三幕火山岩浆作用事件:第一幕约为102Ma发生的强烈火山喷发;第二幕约为92Ma的闪长岩侵入作用;第三幕约为86Ma的闪长玢岩体侵入作用。锆石的Hf同位素原位分析结果表明,主要测点的εHf(t)值在+2.5~+7.9之间,平均值为+4.4,其一阶段Hf模式年龄为505~678Ma,表明白垩纪中期出露的火成岩可能由新元古代-寒武纪的亏损地幔物质部分熔融所形成。结合前人研究成果,得出本岛出露的火成岩形成于冈瓦纳古陆裂解过程所伴生的俯冲岛弧环境中,是构成南 The Antarctic Peninsula, located in the western margin of Gondwana for a long time, was the final place of the Gondwana dispersion. Voluminous Mesozoic-Cenozoic igneous rocks occur in the Antarctic Peninsula, and the magmatic process, source characteristics and geodynamic setting of these rocks remain controversial. This has led to the argument for the tectonic evolution of the Antarctic Peninsula This paper reports zircon LA-MC-ICP-MS U-Pb dating and Hf isotopes of the andesitic volcanic rock, diorite porphyrite vein and diorite xenolith from the Curverville Island in the central domain of the Antarctic Peninsula. The results show that the zircon U-Pb ages are 103.3 +/- 1.7Ma for andesitic breccia lava, 101.9 +/- 1.8Ma for andesitic breccia, 92.0 +/- 1.2Ma for medium grained diorite xenolith, and 85.7 +/- 07Ma for diorite porphyrite vein. This suggests that there existed three episodes of volcanism in the Mid-Cretaceous, with the first episode of intensive volcanic eruption at ca. 102Ma, the second episode of diorite intrusion at ca. 92Ma, and the third episode of diorite porphyrite intrusion at ca. 86 Ma. The in-stiu zircon Hf isotopic analysis indicates that most epsilon(Hf) (t) values are +2.5 similar to +7.9, with an average value of +4.4. Their Hf model ages ranging from 505 Ma to 678 Ma, suggesting that the Mid-Cretaceous igneous rocks may have been derived from the partial melting of depleted mantle materials of the Neoproterozoic-Cambrian age. Coupled with the available published data, we propose that the igneous rocks from the Curverille Island formed in an island arc setting, which accompanies with the process of the Gondwana breakup. Therefore, the igneous rocks from the Curverille Island are one of the main lithology that makes up the central magmatic domain of the Antarctic Peninsula. 国家自然科学基金项目; 国家极地专项; 国土资源大调查项目联合资助 SCI(E) 03 978-992 33